The New Hazardous Jobs and Worker Reallocation - Gaetano Basso; Tito Boeri; Alessandro Caiumi; Marco Paccagnella (Institute of Labor Economics (IZA), 2020)
This paper analyses several dimensions of workers' safety that are relevant in the context of a pandemic. We provide a classification of occupations according to the risk of contagion: by considering a wider range of job characteristics and a more nuanced assessment of infection risk, we expand on the previous literature that almost exclusively looked at feasibility of working from home. We apply our classification to the United States and to European countries and we find that roughly 50% of jobs in our sample can be considered safe, although a large cross-country variation exists, notably in the potential incidence of remote working. We find that the most economically vulnerable workers (low-educated, low-wage workers, immigrants, workers on temporary contracts, and part-timers) are over-represented in unsafe jobs, notably in non-essential activities. We assess the nature of the reallocation of workers from unsafe to safe jobs that is likely to take place in the years to come, and the policies that could mitigate the social cost of this reallocation.
Keywords: J28; J23; J81; 330; working conditions; workers' reallocation; COVID-19; pandemic